Proses Terjadinya Kesalahan Dalam Penalaran Proposional Berdasarkan Kerangka Kerja Asimilasi dan Akomodasi - Samsul Irpan (Beta: Jurnal Tadris Matematika, 2010)
Proportional reasoning is a reasoning of understanding the equal of two relation structure in proportional problem. The error of proportional reasoning is the occurrence of the reasoning error process begins with the less of the reasoning problem that resulting the reasoning process unsuitable to the structure problem. This research is conducted to the students of MTs Surya Buana Kota Malang that had been received the material about comparison (Proportion). The data collection is taken by the Think-Out-Loud (TOL) method or think loud. In TOL method, student is asked to speak loudly what he/she being thought. The data that had been reached will be encoded and become the base to study the error occurrence, when conducting the proportion problem. From this research, I found that the occurrence of reasoning error in the students has some characteristics, they are: (1). The mistake of assimilation process in the subject’s reasoning structure is occur (S1). (2). The less of the reasoning structure in the assimilation process in the meadium member of the subject is happen (S3 and S4). Meanwhile, subject (S2, S5 and S6) have the complete reasoning. This research is limited into the occurrence of the error in proportional reasoning (especially in the equal score comparison). So that, there are another opportunities to the next research especially related to: (1). How is the student’s reasoning when they study about opposition score comparison, and (2). The study design that can decrease the reasoning error in overcoming the math problem.